2010
DOI: 10.1523/jneurosci.3317-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2 Ablation Ameliorates Alzheimer's Disease-Linked Synaptic Dysfunction and Cognitive Deficits

Abstract: Growing evidence implicates aberrant lipid signaling in Alzheimer's disease (AD). While phospholipases A2 and C have been recentlyshown to mediate key actions of amyloid ␤-peptide (A␤) through a dysregulation of arachidonic acid and phosphatidylinositol-4,5-bisphosphate metabolism, respectively, the role of phospholipase D (PLD) has so far remained elusive. PLD produces phosphatidic acid (PA), a bioactive lipid involved in multiple aspects of cell physiology, including signaling and membrane trafficking proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 65 publications
9
169
2
Order By: Relevance
“…32:1 and 34:2) was also observed. These data are in contrast to the specific increase of PA 34:2 seen in a different strain of Swedish APP transgenic mice that were also older in age (11). To determine whether this was an age-related phenomenon, we conducted a targeted PA analysis of 14 -15-month-old APP mice of the same genetic background and found that PA 34:2, and to a lower extent other molecular species of PA, were indeed elevated in these mice relative to 9 -11-month-old APP mice (supplemental Fig.…”
Section: B D and E)contrasting
confidence: 98%
See 2 more Smart Citations
“…32:1 and 34:2) was also observed. These data are in contrast to the specific increase of PA 34:2 seen in a different strain of Swedish APP transgenic mice that were also older in age (11). To determine whether this was an age-related phenomenon, we conducted a targeted PA analysis of 14 -15-month-old APP mice of the same genetic background and found that PA 34:2, and to a lower extent other molecular species of PA, were indeed elevated in these mice relative to 9 -11-month-old APP mice (supplemental Fig.…”
Section: B D and E)contrasting
confidence: 98%
“…For instance, ␥-secretase activity is regulated by membrane levels of cholesterol and sphingomyelin (SM) (8). Second, A␤ exerts its cytotoxic effects primarily by perturbing cellular membranes, in part by modulating the activity of phospholipases, such as PLA 2 (9), PLC (10), and phospholipase D 2 (PLD 2 ) (11). Third, lipids, such as ganglioside GM1, modulate the pathogenic potential of A␤ by affecting its propensity to aggregate (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study showed that genetic ablation of PLD2 ameliorated synaptic dysfunction and cognitive decline in models of AD. 38 Therefore, understanding isotype-specific effects of PLD would be necessary for identifying effective therapeutic strategies targeting PLD enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many studies identified intracellular mediators of the A␤ peptide neurotoxic effects. These intracellular targets include membrane-phospholipid remodeling enzymes such as synaptojanin and phospholipase D (Berman et al, 2008;Oliveira et al, 2010) or signaling proteins such as fyn kinase, glycogen synthase kinase-3␤, cyclin-dependent kinase-5 (Crews and Masliah, 2010). Some inhibitors of these putative therapeutic targets have been proposed because of their potential specificity.…”
Section: Discussionmentioning
confidence: 99%